2017
DOI: 10.1002/ecs2.1686
|View full text |Cite
|
Sign up to set email alerts
|

Browsing impacts on the stable isotope composition of chaparral plants

Abstract: Abstract. We assessed the effects of herbivory on competition, water stress, and potentially biological nitrogen fixation on three species of endemic shrubs using variations in the stable isotope ratios ( C values may be due to increased water stress with substantial shrub growth. More broadly, herbivore suppression of N fixation may impact ecosystem processes such as productivity and N cycling, as well as an ecosystem's ability to respond to increased CO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 72 publications
0
13
1
Order By: Relevance
“…Greater N uptake could be due to greater availability of soil N or greater assimilation rates. Greater N assimilation rates in harvest sites might be the mechanism by which plants have greater δ 15 N values (Cernusak et al, 2009;Koch & Fox, 2017). However, in our study, we found no difference in soil δ 15 N in control and harvest sites (Figure 3) even though soil and foliar δ 15 N were positively correlated (Figure 6a).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Greater N uptake could be due to greater availability of soil N or greater assimilation rates. Greater N assimilation rates in harvest sites might be the mechanism by which plants have greater δ 15 N values (Cernusak et al, 2009;Koch & Fox, 2017). However, in our study, we found no difference in soil δ 15 N in control and harvest sites (Figure 3) even though soil and foliar δ 15 N were positively correlated (Figure 6a).…”
Section: Discussioncontrasting
confidence: 58%
“…This suggests that changes in foliar δ 15 N were not only mediated through soil but though other actions mediated by harvest as well. Greater N assimilation rates in harvest sites might be the mechanism by which plants have greater δ 15 N values (Cernusak et al, 2009;Koch & Fox, 2017). If changes in plant δ 15 N affected plant quality by increasing N availability in leaves (Fang et al, 2011;Hobbie, Macko, & Williams, 2000), then this may explain increases in herbivore abundances following harvest (and subsequent reducing in trophic feeding by ants).…”
Section: Discussionmentioning
confidence: 99%
“…Soil texture (coarse and fine particle size) is one of the most important controls of δ 13 C. Wynn and Bird [76] reported that the <63 µm (percent of mineral particles) fraction is more 13 C enriched than bulk soil, and the >63 µm fractions are more 13 C depleted in Australia. Koch and Fox [77] investigated the relationship between δ 13 C and δ 15 N values and soil depth changes after grazing exclusion on the central Californian coast, and found that the δ 13 C values did not change with depth and there was an increase in δ 15 N values with depth in the fine soil. However, this conclusion is inconsistent with the results of previous studies [36], which may be due to significant differences in the soil respiration rates and subsurface soil structure for various vegetation types.…”
Section: Soil Physical Factorsmentioning
confidence: 99%
“…Variations in composition and spatial structure of the plant community reflect demographic and physiological processes affecting shrubs, herbaceous plants, plant–plant interactions, and plant–herbivore interactions, all mediated in the context of changes in the abiotic environment (Coale et al, 2011; Deveny & Fox, 2006; Fox, 2007; Fox et al, 2006; Pittermann et al, 2014). This initial work indicated that browsing is a key interaction in this system (Coale et al, 2011; Fox, 2007; Koch & Fox, 2017), but the diverse biotic and abiotic impacts of browsing have not previously been integrated into causal pathways of interactions across the community.…”
Section: Introductionmentioning
confidence: 99%
“…Another component of the vegetation—the small, often annual, herbaceous plants that account for most of the endemic biodiversity of chaparral communities—is eaten by deer, woodrats, rabbits, and mice (Fox, 2007 and L. R. Fox, personal observation). A different, but indirect, effect of deer browsing is the suppression of atmospheric nitrogen fixation by bacterial symbionts ( Frankia ) in Ceanothus roots (Koch & Fox, 2017). These top‐down interactions affect all components of the vegetation, with long‐term implications for both community structure and community dynamics.…”
Section: Introductionmentioning
confidence: 99%